2016
DOI: 10.1038/tpj.2016.24
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and implications of cytochrome P450 substrates in Massachusetts hospital discharges

Abstract: The cytochrome P450 (CYP450) system of drug-metabolizing enzymes may contribute to individual variation in drug response. We examined prevalence of CYP450 substrates at hospital discharge for patients in two cohorts: insurance claims of Massachusetts residents and the medical records of two academic medical centers. The claims cohort included 47 473 individuals (38.2%) treated with at least one CYP450 2D6, 2C19, 3A4 or 1A2 substrate. The electronic medical records cohort included 45 905 individuals (57.4%) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
3
2
Order By: Relevance
“…Finally, we cannot distinguish test-specific effects from expectancy or placebo-like effects: tested individuals would be likely to anticipate benefit of test-guided treatment. Prior work suggested that pharmacogenetic testing with this assay increased adherence, but the present data did not allow us to examine the extent to which benefits may be mediated by improved adherence (McCoy et al, 2017). On the other hand, the reduction of 'hard' utilization outcomes, rather than, for example, clinician-assessed severity, suggests that placebo effects or improvement in adherence would need to be substantial.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Finally, we cannot distinguish test-specific effects from expectancy or placebo-like effects: tested individuals would be likely to anticipate benefit of test-guided treatment. Prior work suggested that pharmacogenetic testing with this assay increased adherence, but the present data did not allow us to examine the extent to which benefits may be mediated by improved adherence (McCoy et al, 2017). On the other hand, the reduction of 'hard' utilization outcomes, rather than, for example, clinician-assessed severity, suggests that placebo effects or improvement in adherence would need to be substantial.…”
Section: Discussioncontrasting
confidence: 73%
“…Prior work suggested that pharmacogenetic testing with this assay increased adherence, but the present data did not allow us to examine the extent to which benefits may be mediated by improved adherence(McCoy et al, 2017). On the other hand, it is possible that clinicians order the test for less ill patients, while there is no evidence that this is the case based on cost prior to testing, if it were not addressed by propensity score matching this could falsely inflate the observed benefit.Second, the present study does not allow direct measurement of clinical efficacy and quality of life using standardized instruments or scales, another potential source of confounding.…”
contrasting
confidence: 58%
See 2 more Smart Citations
“…Cohort studies using claims data or electronic health records found that treatment with medications metabolized through the cytochrome P450 system was associated with greater medical cost and readmission, after accounting for differences in comorbidity, suggesting an opportunity to reduce cost by measuring this variation (McCoy, Castro, Cagan, Roberson, & Perlis, 2017). Naturalistic cost‐effectiveness studies likewise suggest that testing for common genetic variation may be associated with improved treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%